COVID-19 related conspiracy beliefs and their relationship with defense strategies, emotions, powerlessness, attitudes, and time perspective - Celia, Giovanna; Lausi, Giulia; Girelli, Laura; Cavicchiolo, Elisa; Limone, Pierpaolo; Giannini, Anna Maria; Cozzolino, Mauro (Frontiers in Psychology, 2022)
The COVID-19 pandemic has greatly impacted individual’s life and society, and such an emergency has increased the likelihood of recurring conspiratorial thinking. There is much research on broader conspiratorial thinking and studies on COVID-19-related conspiratorial thinking has been growing worldwide, moreover, the negative consequences of COVID-19 specific conspiratorial beliefs for people’s health are clear. However, research on conspiratorial theorists’ typologies that combine COVID-19 specific conspiratorial beliefs with other individual features is still scarce. This study contributes by combining the COVID-19 conspiratorial beliefs with defense strategies, emotions, powerlessness, attitudes toward COVID-19, and temporal perspective. A sample of 1.002 people (18-40 years old, M = 23; SD = 5.19) responded to a questionnaire administered online. The aim was to classify people based on their beliefs about COVID-19 conspiracy theories and to examine the clusters’ features associated with automatic defense mechanisms, coping strategies, powerlessness, positive and negative affects, emotional regulation, attitudes toward the COVID-19, social distancing discontent, perceptions of COVID-19 severity and temporal perspective. A k-mean cluster analysis identified three groups: Believers (22.26%), Ambivalent believers (34.3%), and Non-believers (43.21%). Apart by COVID-19-related conspiratorial beliefs, these groups differed mainly by defense mechanisms, and time perspective. These results highlighted the need to tailor interventions for diverse groups of individuals believing in COVID-19 conspiratorial theories.